2008
DOI: 10.1038/nm1718
|View full text |Cite
|
Sign up to set email alerts
|

Breast milk–mediated transfer of an antigen induces tolerance and protection from allergic asthma

Abstract: Allergic asthma is a chronic disease characterized by airway obstruction in response to allergen exposure. It results from an inappropriate T helper type 2 response to environmental airborne antigens and affects 300 million individuals. Its prevalence has increased markedly in recent decades, most probably as a result of changes in environmental factors. Exposure to environmental antigens during infancy is crucial to the development of asthma. Epidemiological studies on the relationship between breastfeeding a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
324
2
8

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 380 publications
(350 citation statements)
references
References 29 publications
16
324
2
8
Order By: Relevance
“…Cite this article as Cold Spring Harb Perspect Biol 2017;9:a022236 Hughes et al 2000;Saarinen et al 2000;Ogawa et al 2004;Verhasselt et al 2008;Verhasselt 2010;Arnold et al 2011). …”
Section: Regulation Of Immunity By Tgf-bunclassified
“…Cite this article as Cold Spring Harb Perspect Biol 2017;9:a022236 Hughes et al 2000;Saarinen et al 2000;Ogawa et al 2004;Verhasselt et al 2008;Verhasselt 2010;Arnold et al 2011). …”
Section: Regulation Of Immunity By Tgf-bunclassified
“…A reciprocal process, trafficking of maternal cells across the placenta, has also been documented (4,5) and can result in life-long microchimerism in the offspring (6). In addition, maternal cells and HLA proteins are ingested by the baby during nursing, possibly stimulating oral tolerance (7,8). However, the mechanisms by which NIMAs actually drive the immune system toward tolerance or rejection of allograft are still unclear.…”
mentioning
confidence: 99%
“…In contrast, Kanda et al (15) described that a substantial proportion of long-term survivors after NIMA-mismatched HSCT could discontinue administration of immunosuppressive agents despite the frequent occurrence of moderate to severe chronic GVHD. Thus, the immunologic effects of developmental exposure to NIMAs are heterogeneous (8,16,17).…”
mentioning
confidence: 99%
“…To guarantee the uptake of TGF , TGF receptors are abundantly expressed in the neonatal intestine, even the soluble TGF 2 receptor is present in breast milk. But in addition it was found that TGF is not essential for tolerance induction when milk born-IgG antigen immune complexes are present (Verhasselt, Milcent et al 2008). Moreover it is known that high levels of TGF together with RA skew the immune system towards a regulatory suppressive function, a low dose of TGF combined with IL6 or IL21 or IL23 will result in inflammatory Th17 activation instead of Treg upregulation (Konkel and Chen 2011).…”
Section: Cytokinesmentioning
confidence: 99%